2021
DOI: 10.3390/fermentation7030118
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient 2,3-Butanediol Production by Bacillus licheniformis via Complex Optimization of Nutritional and Technological Parameters

Abstract: 2,3-Butanediol (2,3-BD) is a reagent with remarkable commercial use as a platform chemical in numerous industries. The present study aims to determine the capabilities of non-pathogenic and cellulolytic Bacillus licheniformis 24 as a 2,3-BD producer. By applying the Plackett–Burman design and response surface methodology through central composite design (CCD), a complex optimization of medium and process parameters was conducted. Thus, among ten studied factors of medium content, four components were evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
2
14
0
Order By: Relevance
“…Different media compositions including yeast extract, tryptone, (NH 4 ) 2 SO 4 , KH 2 PO 4 , K 2 HPO 4 , MgSO 4 , ammonium acetate, etc. were investigated [ 30 ]. They found that both yeast extract and tryptone had positive effects on the production of 2,3-BDO with yeast extract showing the most influencing effect on the fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…Different media compositions including yeast extract, tryptone, (NH 4 ) 2 SO 4 , KH 2 PO 4 , K 2 HPO 4 , MgSO 4 , ammonium acetate, etc. were investigated [ 30 ]. They found that both yeast extract and tryptone had positive effects on the production of 2,3-BDO with yeast extract showing the most influencing effect on the fermentation.…”
Section: Resultsmentioning
confidence: 99%
“…The design of Plackett‒Burman is shown in Additional file 1 : Table S1. The influence of each factor on alkaline protease production was described by the first-degree mode: where Y is the predicted response for alkaline protease activity (the response), β 0 is the model intercept term, β i is the linear coefficient, and X i is an independent variable (Tsigoriyna et al 2021 ). All experiments were conducted in triplicate.…”
Section: Methodsmentioning
confidence: 99%
“…As shown in Figure 3, for the most part acetoin generation still outpaces 2,3-BDO production in this oxygen limited environment. It is probable that the acetoin production by P. polymyxa is being influenced by exhausting or being in the presence of limited glucose content which allows the microbe to consume 2,3-BDO as a carbon source under this stress (Tsigoriyna et al, 2021). To evaluate whether greater 2,3-BDO titers could be achieved a hydrolysate from lignocellulosic biomass was produced and fermented under similar conditions.…”
Section: Figurementioning
confidence: 99%